Phenotypic characteristics of isolates of Aspergillus section Fumigati from different geographic origins and their relationships with genotypic characteristics - Frias-De Leon, Maria Guadalupe (2011)
Fil: Frias-De Leon, Maria Guadalupe. Universidad Nacional Autónoma de México (UNAM). Laboratorio de Micología Molecular; México.